PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI SATUAN POLISI PAMONG PRAJA KOTA BENGKULU - Setiawan, Yongky Aldo; Fitri, Marliza (UM. Bengkulu, 2024)
This study aims 1) to determine the effect of leadership style on the performance of the Bengkulu City Civil Service Police Unit. 2) To determine the effect of work motivation on the performance of the Civil Service Police Unit employees of Bengkulu City. 3) To find out the effect of leadership style and work motivation on the performance of Bengkulu City Civil Service Police Unit employees. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all employees of the Bengkulu City Civil Service Police Unit totaling 60 employees, the following conclusions can be drawn: 1) There is an influence of leadership (X1) on employee performance (Y) Bengkulu City Civil Service Police. 2) There is an influence of motivation (X2) on employee performance (Y) Bengkulu Civil Service Police Bengkulu City 3) There is a joint influence of leadership, work motivation and work discipline on the performance of Bengkulu Civil Service Police officers in Bengkulu City. Keywords: Leadership Style, Work Motivation, Performance